Compact X-Band electron linac for radiotherapy and security applications. (August 2021) - Kutsaev, S.V.; Agustsson, R.; Arodzero, A.; Berry, R.; Bezhanov, A.; Boucher, S.; Chimalpopoca, O.; Diego, A.; Faillace, L.; Gavryushkin, D.; Harrison, M.; Hartzell, J.J.; et al.
Abstract: RadiaBeam has developed a 6 MeV accelerator that is compact and light enough to be placed on a robotic arm or light truck. The main drivers of size and weight in conventional accelerators are the power source and the shielding. Small dimensions are enabled by operation at 9.3 GHz frequency (X-band), which allows reducing the size and weight of all accelerator components. Thanks to the robust design of the accelerating structure, the accelerator can be used as a source for novel cargo inspection and radiotherapy techniques. In this paper, we present the linac design and its components, as well the results of the experimental demonstration of beam acceleration. Highlights: 4π radiotherapy requires accelerator, capable of rotating around the patient. Mobile cargo inspection systems must fit non-commercial chassis. RadiaBeam has developed a compact X-band 4–6 MeV linear accelerator. The linac system is twice more compact comparing to commercial analogs.